The awareness of life cycle costing among architects / Nor Azlinda Mohamed Sabli...[et al.] - Mohamed Sabli, Nor Azlinda; Razali, Mohd Abdul Hadi Siddiqin; Syed Alwee, Sharifah Nur Aina; Maisham, Mysarah (Universiti Teknologi MARA, Kedah, 2019)
Life cycle costing (LCC) is a method of accessing the total cost of facility ownership and has been used in foreign countries for the last few decades. Even though it has been used widely in the foreign countries, our country still far behind as the application of the LCC is not been used wide enough. In fact of that, in order to increase the usage of LCC technique in Malaysia, each party that involved in the industry should have their own awareness to implement the technique in our industry. The implementation of LCC technique in Malaysia construction industry will lead to a greater success in the field and will brings good increasingly-competitive business environment, dwindling resources and an ever-increasing need to obtain value for money in all areas of corporate activity. It is essential to plan and monitor assets throughout their entire life cycle, from the development until the completion of the project. Therefore, the main aim of this paper is to measure the awareness of LCC among the architects since the implementation of LCC should start at the design stage. Feedbacks obtained from the questionnaire survey has shown that there are still lack of awareness among architects about LCC implementation during inception and briefing stage and this may lead into a few issues in light of the fact that LCC is one of the vital components in bringing the value for money to the construction projects. In-depth study of LCC is the crucial factor to be considered at the early stage of the project, in order to ensure the good returns and the best value for money to clients.